Optimization of Theophylline Tablet Formula Using CoProcessed Excipients of Lactose and Avicel - Hayatus Sa`adah; Achmad Fudholi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Tablet excipients in direct compression should have good flowability and compactibility. Improvement of excipients properties may be obtained by coprocessing. Co-processing is defined as combining two or more excipients by an appropriate process. Co-processed excipients of lactose and avicel, which were fabricated by spray drying technique, would be used as filler-binder in theophylline tablet formulation. The co-processed excipients were evaluated for their physical properties, i.e; particle size distribution, average diameter, density, flowability, compactibility and water absorption. Simplex lattice design was used for optimizing flowability, compactibility and water absorption of coprocessed excipients. The results showed that proportion of lactose and avicel with optimum physical properties was determined by the ratio 1:1 with a response of flowability was 8.79 ± 0.02 seconds, compactibility was 5.61 ± 0.08 kg and water absorption was 61.30 ± 0.40 mg/min. Superimposed contour plot of theophylline tablet formulation using co-processed excipients as filler-binder by factorial design was determined by the optimum proportion of magnesium stearate and eksplotab (1:3.74) with the response of hardness was 5.54 ± 0.042 kg, friability was 0.303 ± 0.015%, disintegration time was 1.83 ± 0.115 minutes and DE20was 85.66 ± 0.35%.Key words: theophylline tablets; co-processed excipients; lactose; avicel